Mean Corpuscular Volume as a Prognostic Factor for Patients With Habitual Alcohol or Tobacco Use After Esophagectomy - Huang, Shu-jie; Zhan, Peng-fei; Chen, Shao-bin (Frontiers in Oncology, 2021)
Background: The goal of this study was to investigate the impact of mean corpuscular volume (MCV) in patients with esophageal squamous cell carcinoma (ESCC) who underwent surgical resection. Methods: A total of 615 patients with ESCC who underwent esophagectomy were analyzed. Patients were divided into two groups according to the standard MCV: the high MCV group (>100 fl) and the low MCV group (≤100 fl). Survival analyses were performed to calculate overall survival (OS) and cancer-specific survival (CSS) and investigate the independent prognostic factors. Results: Fifty-one patients (8.3%) were in the high MCV group, and the other 564 patients (91.7%) were defined as the low MCV group. MCV was significantly correlated with sex, habitual alcohol or tobacco use, tumor length, body mass index, and multiple primary malignancies (P < 0.05). Elevated MCV was significantly correlated with poor survival in univariate and multivariate analyses. However, in subgroup analyses, MCV was found to be correlated with survival only in patients with alcohol or tobacco consumption and not in patients without alcohol or tobacco consumption. Conclusions: Pretreatment MCV was correlated with survival in ESCC patients after esophagectomy. However, its prognostic value was only seen in patients with alcohol or tobacco consumption.